Essential concepts are missing: Foreign DNA in food invades the organisms' cells and can lead to stochastic epigenetic alterations with a wide range of possible pathogenetic consequences - Dörfler, Walter (Clinical Epigenetics, 2020)
In this article, a new concept for general pathogenesis has been proposed. Advances in molecular genetics have led to the realization that essential concepts in the framework of molecular biology are still missing. Clinical medicine is plagued by similar shortcomings: The questioning of current paradigms could open new vistas and invite challenging approaches. This article presents an unconventional idea. Foreign DNA which is regularly ingested with the essential food supply is not completely degraded. Small quantities of fragmented DNA rather persist transiently in the gastro-intestinal tract of mice and can be traced to various organ systems, except for cells in the germ line. Foreign DNA entering and persisting in mammalian cells can stochastically lead to genome-wide alterations of transcriptional and CpG DNA methylation profiles. In the course of food-ingested DNA invading somatic cells, completely new cell types can be generated which might be involved in the causation of common ailments. Projects emanating from this perception merit critical analysis and rigorous pursuit.
CRIS-Team Scopus Importer:2020-02-18
Keywords: A new concept in general pathogenesis; Epigenetic alterations upon foreign DNA intrusions; Foreign DNA in mammalian cells and organisms; Origin of novel cell types; Relevance for pathogenesis of common human diseases; Stochastic alterations of cell type; Uptake and persistence of food-ingested foreign DNA